1995
DOI: 10.1103/physrevlett.75.866
|View full text |Cite
|
Sign up to set email alerts
|

Type I Band Alignment inSi1xGex/Si(001<

Abstract: We present experimental verification of a type I conduction band alignment for coherently strained Si~,Ge, layers in (001) silicon, with 0.15~x~0.38. A novel substrate bending scheme is used to apply in-plane uniaxial compressive and tensile stress along the [100] and [110] directions. Band edge photoluminescence from SiGe and Si is shifted with stress in accordance with deformation potential theory. Tensile stress along [110]allows clear distinction between types I and II band alignment where the predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 21 publications
(4 reference statements)
1
29
0
Order By: Relevance
“…For both types of stress, the high excitation data shows good agreement with the blueshift calculated for type I transitions, which also is in agreement with the results reported in Refs. [16] and [17] and is consistent with the relatively high excitation levels used in those earlier studies. However, as the excitation level, and thus the charge accumulation, is lowered, we observe a strong deviation from type I behavior above some characteristic stress which decreases with decreasing excitation.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…For both types of stress, the high excitation data shows good agreement with the blueshift calculated for type I transitions, which also is in agreement with the results reported in Refs. [16] and [17] and is consistent with the relatively high excitation levels used in those earlier studies. However, as the excitation level, and thus the charge accumulation, is lowered, we observe a strong deviation from type I behavior above some characteristic stress which decreases with decreasing excitation.…”
supporting
confidence: 89%
“…However, studies of the effects of compressive ͓001͔ uniaxial stresses by the same group produced results which were only consistent with type I alignment, although that conclusion was not explicitly stated [16]. More recently Houghton et al [17] extended that approach and, based on Si 12x2y Ge x ͞Si͑001͒ QW PL shifts under applied ͓110͔ and ͓100͔ uniaxial stresses, concluded that the band alignment was indeed type I. A surprisingly large CB discontinuity of at least 10 meV for x 0.15 was quoted, based on the absence of any indication of a turnover to type II PL up to the highest ͓110͔ tensile stresses studied.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Our partially relaxed Si 0.9 Ge 0.1 ͑ Ϸ 22% ͒ has a remaining strain of 0.33% and its band gap is about 45 meV below that of fully relaxed Si 0.9 Ge 0.1 . Based on previous results showing that the band gap shrinkage results in an upward shift of the valence band, 27,28 also taking into account that the valence band offset is for at least 90% of the band gap difference between Si and strained Si 1−x Ge x as well as between the strained Si 1−x Ge x and the relaxed Si 1−x Ge x for a given Ge content, 27 and finally, setting the valence band of Si equal to the energy reference, the resulting band gap variation diagram as a function of degree of strain in Si 0.9 Ge 0.1 can be deduced and is shown in Fig. 3.…”
Section: ͑4͒mentioning
confidence: 99%
“…Strained Si/SiGe MQWs have been generally accepted that holes in these heterostructures experience potential wells in the SiGe layer and barriers in Si. The situation in conduction band (CB), however, is rather obscure under the influence of alloying and strain effects, resulting in some uncertainty on whether type-I or type-II band alignment is formed in a given multiple quantum well (MQW) structure (14)(15)(16)(17). However, being able to precisely determine the type of alignment has a direct impact on device properties, e.g., type-I alignment offers a larger band-to-band oscillator strength than type II; thus a stronger radiative emission efficiency is expected from type-I devices.…”
Section: Introductionmentioning
confidence: 99%